EFEKTIVITAS PERCEIVED EASE OF USE DAN USER EXPERIENCE TERHADAP BUYING INTENTION DAN CONSUMER ATTITUDE SEBAGAI VARIABEL INTERVENING PADA SHOPEE - Dwi Sukma Wardani; Alshaf Pebrianggara; Rita Ambarwati Sukmono (Mega Aktiva, 2024)
This research aims to determine the effectiveness of perceived ease of use, user experience on buying intention through consumer attitude as an intervening variable. This research uses primary data with a quantitative approach. The sampling technique in this research used the Purposive Sampling method and the number of samples in this research was 165 respondents. The results of this research show that Perceived Ease of Use has a positive and significant effect on Buying Intention, User Experience has a positive and significant effect on Buying Intention, Consumer Attitude has a positive and significant effect on Buying Intention, Perceived Ease Of Use can be mediated by Consumer Attitude on Buying Intention, and User Experience can be mediated by Consumer Attitude towards Buying Intention